The wounded healer: self-rehabilitation of prisoners through providing care and support to physically and mentally challenged inmates - Einat, Tomer (Journal of crime and justice, 2017)
This qualitative study examines the emotional, mental, and therapeutic effects of the role of care workers on mentor prisoners in the Magen Prison (Mind and Body Center) - a male prison for the mentally ill - and analyzes the perceived connection between these emotional processes and their self-rehabilitation. Semi-structured interviews were conducted with all prisoners operating as mentor prisoners in the Magen prison between the years 2012 and 2014 and then thematically analyzed. The main findings of the study show that the role of care worker is perceived by the mentor prisoner as: (a) promoting their ability to find positive existential meaning in their life; (b) significantly contributing to their rehabilitation; (c) having a positive impact on their relationship with the prison staff. It is therefore evident that the provision of support contributes to the development of feelings of responsibility and empathy among mentor prisoners, helping them to manage their own sense of frustration and despair and facilitating cooperation between them and the staff. On a practical level, we recommend that prison systems integrate a maximum number of prisoners with potential for rehabilitation in peer-mentoring programs and similarly beneficial activities.